Hepatic Silicone Granulomas Secondary to Ruptured Breast Implants: A Report of Two Cases. (3rd November 2019) - Hudacko, Rachel; Anand, Kapil; Gordon, Ronald; John, Tina; Catalano, Carolyn; Zaldana, Francisco; Katz, Henry J.; Fyfe, Billie; Rustgi, Vinod
Abstract : The differential diagnosis of hepatic granulomas is vast and includes infections, drugs, immunologic diseases, foreign material exposure, and neoplasia. Silicone, whether directly injected into tissues or used as a filler in breast implants, is known to cause localized granulomatous reactions. It can also migrate to other anatomic locations resulting in granulomatous inflammation at a distance. We report two cases of unsuspected hepatic silicone granulomas in patients undergoing liver biopsy for isolated elevated alkaline phosphatase levels, both with a history of ruptured breast implants. These cases highlight the need for awareness of hepatic silicone granulomas as an etiology of elevated liver enzymes in patients with a history of surgical interventions utilizing silica, such as cosmetic surgery.